Theorizing the affective logic of victimhood in public debates: implications for everyday education practices. Issue 2 (4th March 2023) - Zembylas, Michalinos
ABSTRACT: How does a world of rival victimhoods disrupt our understandings of the educational subject? In which ways do competing claims of victimhood and their connections with justice have an impact on everyday educational practices? These questions are at the heart of this essay. The analysis conceptualizes the affective logic of victimhood as a terrain of struggle over competing claims to suffering, trauma and injury. The argument is that victimhood works by tactically mobilizing effective claims to suffering, trauma or injury for moral and political gains. The paper highlights implications of this analysis for everyday educational practices, discourses and relationships, and discusses the extent to which a pedagogical approach that engages students with the affective claims of victimhood – namely, who claims to be a victim, from which position and to which effects – can offer productive ways of navigating through competing claims of victimhood.